Asupan Zat Gizi Mikro Dan Stunting Pada Anak Balita di Bukit Rawi, Kecamatan Kahayan Tengah, Kabupaten Pulang Pisau - Yetti Wira Citerawati SY; Erma Nurjanah Widiastuti (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2020)
Abstract- Stunting is still a problem in Indonesia, especially in the Central Kalimantan, where the prevalence is still very high compared to the national figure and WHO standards. Stunting is a problem related to nutrient intake and infection. The purpose of this study was to determine the relationship between micronutrients and the incidence of stunting in the working area of ​​the Bukit Rawi Health Center. The design of this research is analytic observational with a case-control method. The sampling technique uses Purposive Sampling. Sample characteristic data were obtained through interviews using a questionnaire while intake data (vitamin A, Fe, zinc, calcium, phosphorus) were obtained through interviews using the SQFFQ form (Semi-Quantitative Food Frequency). Analysis of bivariate data using the Chi-Square test with a tool in the form of SPSS software. Based on the results of the study, 27 (41.5%) were stunted and 38 (58.5%) were not stunted. The average age of toddlers is 28 months with a minimum age of 19.00 months and a maximum age of 58.00 months. There was no significant relationship between the intake of Vitamin A, Fe, Zinc, and Phosphorus on the incidence of stunting (p = 0.987; p = 0.842; p = 0.590; p = 0.523). However, there was a significant relationship between calcium intake and the incidence of stunting (p = 0.032). Toddlers with less calcium intake were 5.09 times more likely to be stunted than toddlers with good calcium intake (95% CI = 1.026 - 25.270), so toddlers with less calcium intake had a probability of experiencing stunting by 83.6%.